The Effect of Kumon English as a Foreign Language Learning Method on Students’ Narrative Text Reading Comprehension - Adilla Amanda; Ashari P Swondo; Enni Maisaroh; Kharuna Humairah; Adinda Adinda (Edumaspul: Jurnal Pendidikan, 2025)
This study looks at how seventh-grade pupils at SMP PAB 2 Helvetia's reading comprehension abilities are affected by the Kumon English as a Foreign Language (EFL) approach. 72 students were split into two groups using a quasi-experimental design: the experimental group (Kumon EFL) and the control group (traditional technique). Pre- and post-tests testing comprehension of key concepts, specifics, and text structure were used to gather data. The instrument demonstrated great reliability (Cronbach's Alpha = 0.838) and good validity (r-table = 0.361). The experimental group showed a considerable improvement (60.53 to 90.53) compared to the control group (61.20 to 76.80), with a t-test significance of 0.000 (p < 0.05), according to the results. The study concludes that the Kumon EFL method effectively enhances students’ reading comprehension, especially in narrative texts, and serves as an innovative learning alternative.